2011
DOI: 10.1002/hbm.21267
|View full text |Cite
|
Sign up to set email alerts
|

Topography, power, and current source density of theta oscillations during reward processing as markers for alcohol dependence

Abstract: Recent studies have linked alcoholism with a dysfunctional neural reward system. Although several electrophysiological studies have explored reward processing in healthy individuals, such studies in alcohol dependent individuals are quite rare. The present study examines theta oscillations during reward processing in abstinent alcoholics. The electroencephalogram (EEG) was recorded in 38 abstinent alcoholics and 38 healthy controls as they performed a single outcome gambling task which involved outcomes of eit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
67
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(77 citation statements)
references
References 165 publications
9
67
1
Order By: Relevance
“…Separation into theta and delta frequency bands revealed greater power for -RPEs in theta, and greater power for +RPEs in delta, supporting results of a number of recent studies (Bernat et al, 2015;Cavanagh, Frank, Klein, & Allen, 2010;Foti et al, 2014;Kamarajan et al, 2012;Marco-Pallares et al, 2008;Mas-Herrero & Marco-Pallarés, 2014).…”
Section: Discussionsupporting
confidence: 83%
“…Separation into theta and delta frequency bands revealed greater power for -RPEs in theta, and greater power for +RPEs in delta, supporting results of a number of recent studies (Bernat et al, 2015;Cavanagh, Frank, Klein, & Allen, 2010;Foti et al, 2014;Kamarajan et al, 2012;Marco-Pallares et al, 2008;Mas-Herrero & Marco-Pallarés, 2014).…”
Section: Discussionsupporting
confidence: 83%
“…In a recent study on reward processing in alcoholics during a gambling task, event-related theta band (3.0–7.0 Hz) oscillations were evaluated during the loss/gain feedback (Kamarajan et al, 2012). The alcoholic group showed significantly decreased theta power during reward processing compared to controls, particularly during the evaluation of loss.…”
Section: Chronic Alcoholism and Neuroelectrophysiologymentioning
confidence: 99%
“…The participants select a bet of either 50¢ or 10¢, and receive feedback of either loss or gain for the selected amount (outcome stimulus, OS). The task details have been described in our previous publications (Kamarajan et al, 2008; Kamarajan et al, 2012; Kamarajan et al, 2015a; Kamarajan et al, 2015b). The inter-stimulus interval between a CS and OS, and between an OS and the next CS is 1500 ms.…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, ERO theta activity underlying feedback/outcome processing of monetary loss and gain (Luu et al, 2003; Gehring and Willoughby, 2004; Luu et al, 2004; Cohen et al, 2007; Kamarajan et al, 2008; Crowley et al, 2014) has been reported to be a highly useful measure to characterize reward circuitry dysfunction in psychiatric conditions (Oberg et al, 2011; Padrao et al, 2013; Andreou et al, 2015), including alcoholism (Kamarajan et al, 2012; Kamarajan et al, 2015a). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation